Analysis of thermal comfort properties of tri-layer knitted fabrics. Issue 1 (31st December 2023) - Premalatha, C.; Kumar, M. Ramesh; Udaya Krithika, S.M.; Prakash, C.
ABSTRACT: The tri-layer knitted fabrics created for the aim of active sportswear have been enhanced with the help of microdenier filament polyester yarn, spun polyester yarn, polypropylene, and cotton in this study. These developed tri-layer knitted fabrics are then examined for the thermal comfort properties. The results evidently showed that Microdenier Polyester/Microdenier Polyester/Cotton tri-layer knitted fabrics combination shows exceptionally appreciable thermal comfort properties due to their structural factors such as filamentous nature, lesser thickness, low areal density, and lesser bulkiness. The effect of fiber chosen also plays a crucial part with respect to the thermal comfort properties of tri-layer fabrics developed. Samples such as Microdenier Polyester/Polypropylene/Cotton, Polypropylene/Microdenier Polyester/Cotton also performed better next to that of the Microdenier Polyester/Microdenier Polyester/Cotton combination because polypropylene also possesses a good wicking characteristic. A poor thermal behavior was found in the Microdenier Polyester/Cotton/Polypropylene sample because of the reasons such as protruding fibers of cotton, increased thickness, high areal density, etc. Also on comparing between the filament and the spun yarn, the filament yarn is highly recommended due to its appreciable behavior. Results evidently show that Microdenier Polyester/Microdenier Polyester/Cotton combination possesses an exceptionally appreciable thermal comfort property.